Perbandingan Tingkat Resiko Terjadinya Dementia Pada Lansia yang Tinggal Bersama Keluarga Dengan Lansia yang Tinggal di Panti Kota Malang - Tania Ica Riswina; Siti Ainun Marufa; Atika Yulianti (Universitas Malahayati Lampung, 2024)
ABSTRACT Dementia is a disorder that often occurs in the elderly characterized by the deterioration of cognitive function in the elderly that can interfere with daily activities over time. Dementia generally begins with memory loss, mood swings, behavioral changes, and can interfere with the social activities of the elderly. Dementia is a heterogeneous syndrome caused by neurological disorders or other medical disorders. Different living environments can affect social activities between the elderly who live in nursing homes and the elderly who live at home with their families. This study aims to determine the differences between the elderly who live at home with their families and the elderly who live in nursing homes in Malang, East Java. This study used an analytic descriptive method, with a cross-sectional approach. The population in this study were the elderly in Pondok Lansia Al-Islah and the elderly in Posyandu RW. 8 Merjosari. The sample in this study was 40 people divided into two groups, 20 elderly people living in nursing homes and 20 elderly people living at home. Data collection used the Hopkins Verbal Learning Test (HVLT) questionnaire to assess the risk of dementia. Independent t-test statistical test was used to determine the difference in the risk of dementia, obtained p value: 0,001. The results of this study can be concluded that there is a difference in the risk of dementia in the elderly who live in nursing homes with elderly who live at home with family Keywords: Lansia, Tingkat Resiko, Dementia ABSTRAK Demensia adalah gangguan yang sering terjadi pada lansia ditandai dengan kemunduran fungsi kognitif pada lasia yang dapat mengganggu aktivitas sehari-hari seiring dengan berjalannya waktu. Lingkungan tempat tinggal yang berbeda dapat mempengaruhi aktivitas sosial antara lansia yang tinggal di panti jompo dengan lansia yang tinggal di rumah bersama keluarga. Penelitian ini bertujuan untuk mengetahui perbedaan antara lansia yang tinggal di rumah bersama keluarga dan lansia yang tinggal di panti jompo kota Malang, Jawa Timur. Penelitian ini menggunakan metode deskriptif analitik, dengan pendekatan cross-sectional. Populasi dalam penelitian ini adalah lansia yang ada di Pondok Lansia Al-Islah, Kota Malang dan lansia yang ada di Posyandu RW. 8 Kelurahan Merjosari, Kota Malang. Sampel pada penelitian ini sebanyak 40 orang yang dibagi menjadi dua kelompok, 20 orang lansia yang tinggal di panti jompo dan 20 orang lansia yang tinggal di rumah. Pengambilan data menggunakan kuesioner Hopkins Verbal Learning Test (HVLT) untuk menilai resiko terjadinya demensia. Digunakan uji statistik independent t-test untuk mengetahui perbedaan resiko terjadinya demensia, didapatkan nilai p value: 0,001. Hasil penelitian ini dapat disimpulkan bahwa ada perbedaan resiko terjadinya demensia pada lansia yang tinggal di panti jompo dengan lansia yang tinggal di rumah bersama keluarga Kata Kunci: Lansia, Tingkat Rasio, Dementia